Synthesis, Physico-Chemical and Antimicrobial Properties of Some Metal (II) -Mixed Ligand Complexes of Tridentate Schiff Base Derives From Β-Lactam Antibiotic {(Cephalexin Mono Hydrate)-4-Chlorobenzophenone} and Saccharin - Al-Noor, Taghreed H; Jarad, Amer J; Hussein, Abaas Obaid (International Journal of Chemical and Process Engineering Research, 2014)
A new Schiff base (4-chlorophenyl)(phenyl methanimine (6R,7R)-3-methyl-8-oxo-7-(2-phenylpropanamido)-5-thia-1-azabicyclo[4.2.0]oct-2-ene-2-carboxylate=HL=C29H24ClN3O4S) has been synthesized from β-lactam antibiotic (cephalexin mono hydrate (CephH)=(C16H19N3O5S.H2O) and 4- chlorobenzophenone. Metal mixed ligand complexes of the Schiff base were prepared from chloride salt of Fe(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II), in 50% (v/v) ethanol – water medium in aqueous ethanol(1:1) and Saccharin(C7H5NO3S) containing sodium hydroxide. Several physical tools in particular; IR, C:H:N , 1H NMR,13C NMR for ligand, melting point, molar conductance, magnetic moment. and determination of the percentage of the metal in the complexes by flame(AAS). The ligand and their metal complexes were screened for their antimicrobial activity against four bacteria (gram +ve) and (gram -ve) [Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus]. The proposed structure of the complexes using the program, Chem office 3D (2006) and the general formula have been given for the prepared mixed ligand complexes [M(Sac)3(L)].